Mobile Distance Learning with PDAs: Development and testing of pedagogical and system solutions supporting mobile distance learners - Rekkedal, Torstein; Dye, Aleksander (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
The article discusses basic teaching-learning philosophies and experiences from the development and testing of mobile learning integrated with the online distance education system at NKI (Norwegian Knowledge Institute) Distance Education. The article builds on experiences from three European Union (EU) supported Leonardo da Vinci projects on mobile learning: From e-learning to m-learning (2000-2003), Mobile learning – the next generation of learning (2003-2005), and the ongoing project, Incorporating mobile learning into mainstream education (2005-2007).